Highly reversible switching from P- to N-type NO₂ sensing in a monolayer Fe₂O₃ inverse opal film and the associated P–N transition phase diagram - Dai, Zhengfei; Lee, Chul-Soon; Tian, Yahui; Kim, Il-Doo; Lee, Jong-Heun (Journal of materials chemistry. A, Materials for energy and sustainability, 2015)
The detection of nitrogen dioxide, NO₂, is currently the subject of extensive scientific and technological research, motivated by its deleterious impact on the environment and on human health and safety. However, detecting trace levels of NO₂ gas in a timely, sensitive, and selective manner remains challenging, while the mechanisms governing selective NO₂ sensing are still unclear. In this work, a monolayer α-Fe₂O₃ inverse opal (IO) film with single-crystalline 3-fold rotocenters is firstly synthesized in situ on a substrate using a sacrificial template and evaluated as a sensitive NO₂ chemiresistor. Interestingly, the Fe₂O₃ macroporous film manifests abnormal sensing behavior with reversible transitions from p- to n-type sensing as a function of the NO₂ concentration (C) and working temperature (T). Based on more familiar phase diagrams, a binary (T–C) transition diagram has been created in terms of the gas sensing response, which can be directly used to design and control the p–n transitions. Further investigations also show that such abnormal p–n transitions do not occur if a different sensing material (e.g. SnO₂ IO) is used, or on exposure to gases other than NO₂. The porous Fe₂O₃ sensor is capable of detecting trace levels of NO₂, as low as 10 ppb, and shows good stability. Finally, the mechanisms underlying the unusual NO₂ sensing transitions are described based on the nature of the materials and the well-known Lennard-Jones model. Reversible switching from p- to n-type sensing and the associated transition diagram carry great potential for the recognition and sensitive detection of trace levels of NO₂.